2015
DOI: 10.1007/s11626-015-9961-4
|View full text |Cite
|
Sign up to set email alerts
|

Augmentation of oxidative stress-induced apoptosis in MCF7 cells by ascorbate–tamoxifen and/or ascorbate–juglone treatments

Abstract: Since reactive oxygen species (ROS) play diverse roles in cancer, modulating the redox status of cancerous cells seems to be a promising therapeutic approach. Oxidant-targeted therapy appears logical for intervention with the acquired adaptive response to oxidative stress in cancer. In this study, we investigated the cytotoxic effects of juglone (J) and tamoxifen (T) and also the combination of each with ascorbate (A): tamoxifen/ascorbate (TA) and/or juglone/ascorbate (JA) on MCF7 cancerous cells. The results … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 47 publications
0
14
0
Order By: Relevance
“…Glutathione (GSH), catalase (CAT), superoxide dismutase (SOD) and glutathione peroxidase protein levels diminished, validating the hypothesis of their consumption by juglone-induced ROS formation [ 93 ]. Juglone-mediated oxidative stress triggered forkhead box O3 (FOXO3), that, in turn, modulated p53 and altered the cellular homeostatic balance, prompting apoptosis [ 93 ]. Another interesting study showed that juglone cytotoxicity is, at least partially, ascribed to DNA damage.…”
Section: Anticancer Activitymentioning
confidence: 63%
See 3 more Smart Citations
“…Glutathione (GSH), catalase (CAT), superoxide dismutase (SOD) and glutathione peroxidase protein levels diminished, validating the hypothesis of their consumption by juglone-induced ROS formation [ 93 ]. Juglone-mediated oxidative stress triggered forkhead box O3 (FOXO3), that, in turn, modulated p53 and altered the cellular homeostatic balance, prompting apoptosis [ 93 ]. Another interesting study showed that juglone cytotoxicity is, at least partially, ascribed to DNA damage.…”
Section: Anticancer Activitymentioning
confidence: 63%
“…Juglone ( Figure 1 ) is a member of this family, acting as a growth-stunting agent [ 136 ] and apoptosis inducer. It exhibits antitumour activity on many types of tumours, such as breast [ 92 , 93 , 94 , 95 , 137 ], skin [ 99 , 100 , 137 ], glial cells [ 109 , 110 , 111 , 135 , 138 ], lung [ 137 , 138 ], prostate [ 105 , 106 , 107 , 137 ], pancreas [ 97 ], bladder [ 108 ], stomach [ 98 ], cervix [ 102 , 103 , 139 , 140 ], ovary [ 104 ], and blood [ 113 , 114 ]. For some of them, the mechanism of action has been investigated.…”
Section: Anticancer Activitymentioning
confidence: 99%
See 2 more Smart Citations
“…Tamoxifen induced a significant reduction in fat mass in adipose mice and transiently stimulated the production of reactive oxygen species (ROS) in these mice in vivo, and in murine adipocytes exposed in vitro (Liu et al 2015). The growth-inhibitory effects of tamoxifen on MCF7 human breast cancer cells were associated with enhanced levels of ROS production and lipid peroxidation (Sajadimajd, Yazdanparast, and Roshanzamir 2016).…”
Section: Additional Informationmentioning
confidence: 99%